Public relations and social responsibility of the Peruvian universities according to the new university law - Kovács Halay, István János (2016)
The new university law 30220, promulgated on July 8, 2014, obliges universities to rethink their social responsibility in order to develop genuine programs of social projection that allow various sectors of society to have the technical knowledge to self-manage their development through the production of new knowledge that are consistent with our multicultural national reality. Universities should develop work Strategic Public Relations consistent in promoting communication channels with the society in which both parties tune interests and participate together in a democratic manner in the design, development and evaluation of such programs Social Responsibility thus promoting integration harmonious on both sides. In addition, it is important that universities report transparently how to manage their resources and thus build confidence in society. To meet the multiple needs of our country, universities must enter into agreements with other universities and companies generally offer better opportunities for professional and personal the whole community that shape development. Social Responsibility university ceased to be a simple charitable assistance to the poorest sectors of society. The new law requires universities to make history in society forming an entrepreneurial mindset among teachers, students and graduates to thereby achieve national progress with equity, a fact that will contribute to the overall development of universities to society.